Acaricidal activity of juazeiro leaf extract against red spider mite in cotton plants - Ferraz, José Cláudio Barros; Matos, Cláudia Helena Cysneiros; Oliveira, Carlos Romero Ferreira de; Sá, Maria das Graças Rosa de; Conceição, Antônia Gilciléia Cunha da (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the toxicity, repellency, efficiency, and phytotoxicity of the aqueous extract of juazeiro (Ziziphus joazeiro) leaves in the control of the red spider mite, Tetranychus ludeni, on cotton plant. For toxicity evaluation, T. ludeni adult females were put on cotton leaf discs sprayed with the juazeiro extract. The repellent effect was verified in arenas that contained cotton leaf discs treated or not with the aqueous extract. The control efficiency of the juazeiro extract was evaluated by the infestation of cotton plants by adult female mites, followed by spraying with the extract. Measured LC50 was 3.54% (m/v), with 76.47% mortality and repellent effect. There was control efficiency for 120 hours, with 78.02% average, without significant difference between the evaluation intervals. Cotton plants did not show phytotoxicity. The juazeiro aqueous extract shows potential as an alternative control of T. ludeni on cotton plant due to its high toxicity, repellent effect, and efficiency in causing mortality, without being phytotoxic to cotton plants.